2022
DOI: 10.1186/s12884-022-04452-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric vulnerability and the risk for unintended pregnancies, a systematic review and meta-analysis

Abstract: Background Unintended pregnancies (UPs) are a global health problem as they contribute to adverse maternal and offspring outcomes, which underscores the need for prevention. As psychiatric vulnerability has previously been linked to sexual risk behavior, planning capacities and compliance with contraception methods, we aim to explore whether it is a risk factor for UPs. Methods Electronic databases were searched in November 2020. All articles in En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 62 publications
2
14
1
Order By: Relevance
“…However, the proportion of unintended pregnancies amongst women who were ever pregnant in our sample was comparable to other samples of women with anxiety and depression (45.4%) [ 20 ]. This confirms the high risk of unintended pregnancies in persons with mental health problems, as previously shown in a review and meta-analysis [ 9 ]. Moreover, as a proportion of women in our sample is in the reproductive phase of life, the lifetime prevalence of unintended pregnancies could increase in our sample.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the proportion of unintended pregnancies amongst women who were ever pregnant in our sample was comparable to other samples of women with anxiety and depression (45.4%) [ 20 ]. This confirms the high risk of unintended pregnancies in persons with mental health problems, as previously shown in a review and meta-analysis [ 9 ]. Moreover, as a proportion of women in our sample is in the reproductive phase of life, the lifetime prevalence of unintended pregnancies could increase in our sample.…”
Section: Discussionsupporting
confidence: 90%
“…Although impaired mental health is an established risk factor for unintended pregnancies [ 9 ], the perspective and preferences of persons with mental health problems on their own family planning are currently lacking. Moreover, most studies have a profound focus on preventing unwanted pregnancies and only a minor interest in studying how desired pregnancies can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…As these analyses are cross-sectional, it is not possible to arrive at conclusions regarding causality, however, it appears more likely to assume that the legal provisions might lead to reduced depression than to assume the reverse. This is because mental health indications, including depression, are themselves associated with increased rates of unplanned pregnancy and requests for induced abortion; if levels of depression among women of childbearing age were driving a liberalization in abortion policy, one would expect findings opposite to those of the current study [15,16,53,54]. The possible mechanisms that could mediate the association in this study include (a) positive effects of abortion on depression in those seeking this procedure for mental health indications, (b) positive effects of abortion on mental health in women living in situations characterized by chronic stress or trauma, such as IPV, and (c) a more general effect among women of childbearing age, in which knowing that legal abortion is available as an option in the event of unforeseen medical, psychological, or interpersonal problems gives them a greater sense of autonomy and control over their reproductive choices [55][56][57].…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, the relationship between mental health, unplanned pregnancy, and abortion is not unidirectional. The presence of common mental disorders is itself associated with an increased rate of unplanned pregnancy in young women [ 15 , 16 ], and several factors that can themselves increase the risk of depression, such as childhood abuse, economic difficulties, gender-based violence, and relational problems with a partner or spouse, appear to influence the link between abortion and subsequent mental health [ 17 ]. In a critical review of the existing literature, Reardon concluded that though there was consistent evidence of a link between abortion and adverse mental health outcomes, this relationship was confounded by factors such as the experience of abortion itself and pre-existing risk factors, leading to significant difficulties in establishing causality [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unplanned pregnancies are common, 5,6 and women with psychiatric disorders may be more likely than the general population to have unplanned pregnancies. 7 We can plan on unplanned pregnancies in our practices. We must treat all women of reproductive potential as if they will become pregnant while taking the prescribed medication, as unplanned pregnancies are commonplace.…”
mentioning
confidence: 99%